Downregulation of miR-145-5p elevates retinal ganglion cell survival to delay diabetic retinopathy progress by targeting FGF5. Issue 9 (2nd September 2019) - Zhang, Jingjing; Cui, Changlei; Xu, Haiyang
ABSTRACT: Diabetic retinopathy (DR) is a leading cause of new-onset blindness. Recent studies showed that protecting retinal ganglion cells (RGCs) from high glucose-induced injury is a promising strategy for delaying DR. This study is to investigate the role of miR-145-5p in high glucose-induced RGC injury. Here, RGCs were randomly divided into low glucose and high glucose groups. PCR assay showed miR-145-5p was significantly upregulated in high glucose group. Transfection of miR-145-5p inhibitor decreased pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) levels, elevated cell viability and proliferation, as well as suppressed cell apoptosis by ELISA, MTT, EdU proliferation, colony formation and flow cytometry assays, respectively. Moreover, dual-luciferase reporter assay confirmed FGF5 as a target gene of miR-145-5p. FGF5 knockdown could partially reverse the protective effects of miR-145-5p on RGC-5 cells. In conclusion, our results demonstrated that inhibition of miR-145-5p might be a neuroprotective target for diabetes mellitus-related DR. Abbreviations: DR: diabetic retinopathy; RGCs: retinal ganglion cells; miR-145-5p: microRNA-145-5p; TNF-α: tumor necrosis factor-α; IL-6: interleukin-6; FGF: fibroblast growth factor; ATCC: American Type Culture Collection; WT: wild type; MUT: mutant type Graphical abstract: : Inhibition of miR-145-5p could protect retinal ganglion cells against high glucose at least in part through up-regulating FGF5 expression.